1995
DOI: 10.1074/jbc.270.40.23780
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor α-induced Phosphorylation of Insulin Receptor Substrate-1 (IRS-1)

Abstract: Tumor necrosis factor-␣ (TNF) has been suggested to be the mediator of insulin resistance in infection, tumor cachexia, and obesity. We have previously shown that TNF diminishes insulin-induced tyrosine phosphorylation of insulin receptor substrate 1 (IRS-1). The current work examines potential mechanisms that mediate this event. TNF effect on IRS-1 in Fao hepatoma cells was not associated with a significant reduction in insulin receptor tyrosine kinase activity as measured in vitro but impaired the associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
148
1
5

Year Published

1997
1997
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 390 publications
(163 citation statements)
references
References 38 publications
9
148
1
5
Order By: Relevance
“…To test this hypothesis in our model, we applied the proteomic approach to study the key protein components involved in the C2C12 insulin resistance model, following FFA chronic treatment. We used the comparative proteomic analysis to screen for different kinases (75), phosphatases [27] and phosphosite proteins [31]. The phosphosite screen clearly showed a significant increase in the phosphorylation of PKCα (122%), PKCβ (631%), PKCδ (351%), and PKCε (698%) isoforms in cells treated with oleate but only alpha (80%) and delta (51%) in cells pretreated with palmitate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To test this hypothesis in our model, we applied the proteomic approach to study the key protein components involved in the C2C12 insulin resistance model, following FFA chronic treatment. We used the comparative proteomic analysis to screen for different kinases (75), phosphatases [27] and phosphosite proteins [31]. The phosphosite screen clearly showed a significant increase in the phosphorylation of PKCα (122%), PKCβ (631%), PKCδ (351%), and PKCε (698%) isoforms in cells treated with oleate but only alpha (80%) and delta (51%) in cells pretreated with palmitate.…”
Section: Discussionmentioning
confidence: 99%
“…PKC activation has been implicated in several studies of insulin resistance and diabetes and even in the absence of lipid oversupply [11,25,26]. The inhibitory effects of PKC on insulin signaling may at least in part be explained by the more recently identified role of the serine/ threonine phosphorylation of IRS-1, which has been implicated in the inhibition of its tyrosine phosphorylation [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…N GMethyl-L-arginine, FPT inhibitor II, and antibodies against mouse macrophage iNOS were obtained from Calbiochem. [␥- 32 Isolation and Maintenance of Astrocytes and C 6 Glial Cells-Astrocytes were prepared from rat cerebral tissue as described by McCarthy and DeVellis (14). Cells were maintained in DMEM/F-12 containing 10% fetal bovine serum.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent studies have indicated that, through the p55 TNF receptor (58), TNF-␣ can interfere with the insulin signaling pathway by impairing insulin-induced tyrosine phosphorylation of both the insulin receptor and insulin receptor substrate-1 (IRS-1) (59 -63). It has been shown that a serine phosphorylation of IRS-1 (64,65) converts this protein into an inhibitor of the insulin receptor tyrosine kinase activity. In contrast with these investigators, Stephens et al (66) have very recently suggested that the primary mechanism for TNF-␣-induced insulin resistance was rather the reduced mRNA transcription of several genes involved in the insulin-stimulated glucose transport.…”
Section: Table IV Effect Of Tnf-␣ Treatment On the Lipolytic Activitymentioning
confidence: 99%